Development of a prototype mechanical boundary maker for vegetable crop / Luqman Nul Hakim Jamaluddin - Jamaluddin, Luqman Nul Hakim (2023)
This project is to design the mechanical tool to set the boundary. The reason why this tool was designed is to replace the tool that smallholders use to set the boundaries. This product was focusing to smallholders. This is due to the fact that large-scale plantations already make use of cutting edge equipment which is the tool or machine used were highly cost and smallholders cannot afford to buy it. Therefore, this product was designed to help them use the tool to set the boundaries. Therefore, the expectation for this product is to help the smallholder. Hopefully, they will not face the same problem over and over again before they use this product. The initiative will make it simple for them to set the boundaries. Lastly, smallholders will have the opportunity to employ this product's output for their gardens